EpCAM is predominantly expressed in high grade and advanced stage urothelial carcinoma of the bladder. Issue 3 (22nd June 2007) - Brunner, A; Prelog, M; Verdorfer, I; Tzankov, A; Mikuz, G; Ensinger, C
Abstract : Background: EpCAM is an adhesion molecule of the basolateral membranes in a variety of epithelial cells. Over-expression has been detected in many epithelial tumours and has been associated with high stage, high grade and a worse survival in some tumour types. Aims: To assess the prognostic value of EpCAM in urothelial carcinoma of the bladder. Methods: EpCAM expression was analysed by immunohistochemistry using a monoclonal antibody (clone VU-1D9) on a tissue microarray comprising 99 urothelial carcinomas of the bladder diagnosed between 1994 and 1997. Results: A significant relationship between high grade, advanced stage, and EpCAM expression was found, and expression of EpCAM was associated with a worse overall survival when compared to EpCAM negative tumours (p = 0.033). Multivariate analysis showed that EpCAM expression was not an independent prognostic factor for overall survival in urothelial carcinoma of the bladder. Conclusion: EpCAM expression is associated with advanced stage, high grade and poor overall survival in urothelial carcinoma of the bladder, but lacks an independent prognostic significance. The strong association with high grade tumours suggests a possible role during tumour progression and makes EpCAM a potential target for antibody mediated therapy.